PENDAMPINGAN SANTRI MUSHOLLA NURUL HUDA DALAM PENGENALAN BAHASA ARAB DASAR - Zaeni, Akhmad; taubah, Miftachul (INAIFAS Press, 2025)
Assistance for Nurul Huda musholla students in introducing basic Arabic using the ABCD (Asset-Based Community Development) method. The strategy used to achieve the expected goals is divided into three stages, namely (1) Preparation, (2) Implementation, and (3) ) Evaluation. Basic Arabic reading, writing, and basic Arabic speaking. Arabic. Qiroah, Kitabah, Kalam. The source of empowerment was chosen by gathering a number of students from the Nurul Huda Yosowilangun – Lumajang musholla. While the implementation of this service requires only a few participants, because many students of the Nrulu Huda prayer room are still learning to read iqro', after discussing with several ustadz at the Nurul Huda Mosque, only students who can already read the Qur'an are allowed to take part in Arabic learning activities base. the basic Arabic learning method of qiroah, scriptures, and kalam is very effective for helping students of the Nurul Huda Yosowilangun mosque to get to know the basic Arabic language for writing, reading and speaking. This method is very effective for understanding Arabic and can help musholla Nurul Huda students who wish to continue their studies at Islamic boarding schools or advanced levels as a basis or provision for them in the future.